2004
DOI: 10.1084/jem.20040131
|View full text |Cite
|
Sign up to set email alerts
|

CD24 Controls Expansion and Persistence of Autoreactive T Cells in the Central Nervous System during Experimental Autoimmune Encephalomyelitis

Abstract: In the development of experimental autoimmune encephalomyelitis (EAE), a model for multiple sclerosis (MS), autoreactive T cells must be activated and clonally expand in the lymphoid organs, and then migrate into the central nervous system (CNS) where they undergo further activation. It is unclear whether the autoreactive T cells further expand in the CNS and if so, what interactions are required for this process. We have demonstrated previously that expression by the host cells of the heat-stable antigen (CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 35 publications
3
96
0
1
Order By: Relevance
“…Differences in the extent of infiltration by recipient-derived Thy1.2 ϩ T cells were especially notable in these two groups of recipients. The finding that many Thy1.2 ϩ IFN-␥ Ϫ/Ϫ lymphocytes migrated to the thyroids and contributed to L-SAT in the presence of WT lymphocytes is consistent with other reports demonstrating that host T cells could be recruited into inflammatory lesions by donor T cells (23). In contrast, very few recipient-derived Thy1.2 ϩ IFN-␥R Ϫ/Ϫ lymphocytes infiltrated the thyroids of IFN-␥R Ϫ/Ϫ mice given WT lymphocytes even though the IFN-␥R Ϫ/Ϫ lymphocytes could produce IFN-␥ (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Differences in the extent of infiltration by recipient-derived Thy1.2 ϩ T cells were especially notable in these two groups of recipients. The finding that many Thy1.2 ϩ IFN-␥ Ϫ/Ϫ lymphocytes migrated to the thyroids and contributed to L-SAT in the presence of WT lymphocytes is consistent with other reports demonstrating that host T cells could be recruited into inflammatory lesions by donor T cells (23). In contrast, very few recipient-derived Thy1.2 ϩ IFN-␥R Ϫ/Ϫ lymphocytes infiltrated the thyroids of IFN-␥R Ϫ/Ϫ mice given WT lymphocytes even though the IFN-␥R Ϫ/Ϫ lymphocytes could produce IFN-␥ (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…70 Adoptive transfer studies revealed a critical role for CD24 on both T cells and radio-resistant host cells. 70,71 Furthermore, although pathogenic T cells can be recruited at comparable efficiency to the central nervous system of both wild-type and CD24-deficient mice, the T cells persist and expand only in the wild-type central nervous system. In vitro experiments demonstrated that the costimulatory activity of microglia and astrocytes from CD24-deficient mice is reduced.…”
Section: Cd24 and Autoimmune Diseasementioning
confidence: 99%
“…These data suggest that CD24 expressed on microglia and astrocytes may promote the activation and proliferation of pathogenic T cells. 71 Using transgenic mice with a glia-specific promoter, overexpression of CD24 in the central nervous system led to a more severe and progressive disease EAE. 72 The essential role of CD24 expression on T cells in experimental autoimmune encephalomyelitis is not understood.…”
Section: Cd24 and Autoimmune Diseasementioning
confidence: 99%
“…Our recent studies suggest that CD24 expression is increased greatly in EAE lesions and CNS local cells close to the EAE lesion (our unpublished observation). Our previous studies have revealed that CD24 is required for the pathogenesis of EAE (19,22). The development of EAE requires CD24 expression on both T cells and non-T host cells.…”
Section: Xperimental Autoimmune Encephalomyelitis (Eae)mentioning
confidence: 99%